Neues Leistungsstörungs- und Kaufrecht : Eine Zwischenbilanz. Vortrag, gehalten vor der Juristischen Gesellschaft zu Berlin am 14. Januar 2004 - Lorenz, Stephan (Schriftenreihe der Juristischen Gesellschaft zu Berlin ;, 2004)
In this written version of a lecture, the author makes an initial assessment of the Default and Purchasing Act. Both the pseudo-problems and the real problems of this area are illustrated here, as are individual questions of the conformity to guidelines of the new Purchasing Act.